Pengenaan Sanksi Administrasi dalam Penegakan Disiplin Aparatur Sipil Negara - Ahmad Rohmanto; Hartati Hartati; Dony Yusra Pebrianto (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This study aims 1) to determine and analyze the disciplinary regulations of state civil servants; 2) to determine and analyze the imposition of administrative sanctions on the enforcement of disciplinary regulations of state civil servants. The research method used is the normative juridical research method and the approach used is the statutory approach and the conceptual approach. The results of the study indicate that 1) the disciplinary regulations of state civil servants that Government Regulation Number 94 of 2021 was issued in order to implement the provisions of Article 86 Paragraph (4) of Law Number 5 of 2014 concerning State Civil Apparatus (ASN). The body or chapters of the provisions regulated in Government Regulation Number 94 of 2021 are not much different from Government Regulation Number 53 of 2010. However, there are several changes in the number of chapters and points, which are increased or decreased. In relation to the procedures for imposing disciplinary violations according to Government Regulation Number 53 of 2010 and Government Regulation Number 48 of 2016 and Government Regulation Number 94 of 2021 concerning Civil Servant Discipline, civil servants who lose their prestigious rights as civil servants because they have been dishonorably dismissed as civil servants so that they can no longer receive facilities in the form of salaries, allowances and other facilities; 2) the imposition of administrative sanctions against the enforcement of civil servant discipline because even though there is a legal basis that provides legitimacy for the court to order the implementation of rehabilitation of ASN rights, the laws and regulations that specifically regulate the enforcement of ASN discipline still do not clearly regulate rehabilitation. In relation to the provisions of the ASN Law, especially Article 87 Paragraph (4) letter b, it is necessary to reconstruct legal regulations and impose sanctions on ASN employees who have committed criminal acts of corruption. The reconstruction of the legal regulations is carried out through changes and/or improvements by clarifying the formulation of the governing norms and explicitly mentioning "criminal acts of corruption" or implicitly but clarifying and emphasizing the difference between it and "criminal acts of official misconduct or crimes related to office."